This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
It can be done in a shorter way as follows:
Take a = 5 5 5 and b = 5 5 4 . The expression becomes:
a ( 1 0 0 0 b + a ) − b ( 1 0 0 0 a + b ) = = = = = 1 0 0 0 a b + a 2 − 1 0 0 0 a b − b 2 a 2 − b 2 ( a − b ) ( a + b ) 1 × 1 1 0 9 1 1 0 9
Problem Loading...
Note Loading...
Set Loading...
Let a = 5 5 4
Then the given expression can be written as -
( a + 1 ) ( 1 0 0 0 a + a + 1 ) − a [ 1 0 0 0 ( a + 1 ) + a ]
= ( a + 1 ) ( 1 0 0 1 a + 1 ) − a [ 1 0 0 0 a + 1 0 0 0 + a ]
= 1 0 0 1 a 2 + 1 0 0 1 a + a + 1 − 1 0 0 0 a 2 − 1 0 0 0 a − a 2
= a + a + 1
= 2 a + 1
= 2 × 5 5 4 + 1
= 1 1 0 8 + 1
= 1 1 0 9